The Pristine Inner Galaxy Survey (PIGS) II: Uncovering the most metal-poor populations in the inner Milky Way. Issue 4 (17th July 2020) - Arentsen, Anke; Starkenburg, Else; Martin, Nicolas F; Aguado, David S; Zucker, Daniel B; Allende Prieto, Carlos; Hill, Vanessa; Venn, Kim A; Carlberg, Raymond G; González Hernández, Jonay I; Mashonkina, Lyudmila I; Navarro, Julio F; et al.
ABSTRACT: Metal-poor stars are important tools for tracing the early history of the Milky Way, and for learning about the first generations of stars. Simulations suggest that the oldest metal-poor stars are to be found in the inner Galaxy. Typical bulge surveys, however, lack low metallicity ($\rm {[Fe/H]} \lt -1.0$ ) stars because the inner Galaxy is predominantly metal-rich. The aim of the Pristine Inner Galaxy Survey (PIGS) is to study the metal-poor and very metal-poor (VMP, $\rm {[Fe/H]} \lt -2.0$ ) stars in this region. In PIGS, metal-poor targets for spectroscopic follow-up are selected from metallicity-sensitive CaHK photometry from the CFHT. This work presents the ∼250 deg 2 photometric survey as well as intermediate-resolution spectroscopic follow-up observations for ∼8000 stars using AAOmega on the AAT. The spectra are analysed using two independent tools: ULySS with an empirical spectral library, and FERRE with a library of synthetic spectra. The comparison between the two methods enables a robust determination of the stellar parameters and their uncertainties. We present a sample of 1300 VMP stars – the largest sample of VMP stars in the inner Galaxy to date. Additionally, our spectroscopic data set includes ∼1700 horizontal branch stars, which are useful metal-poor standard candles. We furthermore show that PIGS photometry selects VMP stars with unprecedented efficiency: 86 per cent/80 per cent (lower/higher extinction) of the best candidates satisfy $\rm {[Fe/H]} \lt -2.0$, as do 80 per cent/63 per cent of a larger, less strictly selected sample. We discuss future applications of this unique data set that will further our understanding of the chemical and dynamical evolution of the innermost regions of our Galaxy.